2023
DOI: 10.3389/fnins.2023.934341
|View full text |Cite
|
Sign up to set email alerts
|

A review of neuroendocrine immune system abnormalities in IBS based on the brain–gut axis and research progress of acupuncture intervention

Abstract: Irritable bowel syndrome (IBS) is a common digestive disorder observed in clinics. Current studies suggest that the pathogenesis of the disease is closely related to abnormal brain–gut interactions, hypokinesia, visceral sensory hypersensitivity in the gastrointestinal tract, and alterations in the intestinal microenvironment. However, it is difficult for a single factor to explain the heterogeneity of symptoms. The Rome IV criteria emphasized the holistic biologic-psycho-social model of IBS, suggesting that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 109 publications
0
4
0
Order By: Relevance
“…[10,49] In addition, ACU may regulate mood and intestinal function by regulating endocrine functions, such as promoting the secretion of neurotransmitters such as β-endorphins, dopamine, and serotonin. [50,51] Moreover, a growing number of studies support the potential of ACU in the treatment of anxiety and depression. ACU may promote brain neural plasticity, change the functional connectivity and structure of the brain, and then affect emotion regulation and cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…[10,49] In addition, ACU may regulate mood and intestinal function by regulating endocrine functions, such as promoting the secretion of neurotransmitters such as β-endorphins, dopamine, and serotonin. [50,51] Moreover, a growing number of studies support the potential of ACU in the treatment of anxiety and depression. ACU may promote brain neural plasticity, change the functional connectivity and structure of the brain, and then affect emotion regulation and cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study suggested that acupuncture could play a holistic role in regulating inflammatory cytokines, while the function of cytokines is considered as chemical messengers for regulating the innate and adaptive immune systems, 14 and the upstream and downstream mechanism of acupuncture regulates inflammation is still unknown. Currently, the mechanism pathways of acupuncture by means of inflammatory reaction leading to improvement in depressive symptoms can be divided into three types: (1) inhibition of the release of inflammatory cytokines by activating the vagal nerve; 80 (2) regulation of the brain-gut axis through intestinal microbiota; 81 (3) regulation of HPA axis. 82 Moreover, for PPD patients who did not respond after 8 weeks of acupuncture treatment, whether they can achieve significant clinical efficacy by increasing frequency of acupuncture, prolonging treatment courses, or combining with other therapies (such as psychotherapy) needs to be explored in future research.…”
Section: Discussionmentioning
confidence: 99%
“…43 Acupuncture may also modulate the immune system by affecting the activity of immune cells and cytokine production, for example, by adjusting the gut-brain axis, which in turn enhances the body’s resistance to disease. 44 Acupuncture stimulates the body’s own regulatory and reparative mechanisms by altering connective tissue structure and neurotransmitter levels, prompting the flow of energy and blood to rebalance. 45 Finally, acupuncture may produce relaxation and calming effects that help reduce anxiety and improve sleep quality, providing support for the overall health and psychological well-being of patients.…”
Section: Acupuncturementioning
confidence: 99%